Micromechanical modeling approach with simplified boundary conditions to compute electromechanical properties of architected piezoelectric composites. (4th February 2021) - Khan, Kamran A; Al Hajeri, Falah; Khan, Muhammad Ali
Abstract: Architected piezoelectric composites (PCs) have recently gained interest in designing transducers and nondestructive testing devices. The current analytical modeling approach cannot be readily applied to design architected periodic PCs exhibiting elastic anisotropy and piezoelectric activity. This study presents a micromechanical (MM)-model based finite element (FE) modeling framework to predict the electromechanical properties (EMPs) of the architected PCs. As an example, the microstructure with one-dimensional (1–3 PCs) connectivity is considered with different cross-sections of fibers. 3D FE models are developed. The intrinsic symmetry of architected composite is used to derive boundary conditions (BCs) equivalent to periodic BCs (PBCs). The proposed approach is simple and eliminates the need for a tedious mesh generation process on opposite boundary faces on the MM model of architected PCs. The EMPs of 1–3 PCs calculated from the proposed micromechanics-FE models were compared with those obtained from analytical solutions (i.e. based on micromechanics theories), and FE homogenization (i.e. obtained by employing the PBCs available in the literature). A quite good agreement between the proposed modeling approach and the ones obtained using the analytical model was observed. However, an excellent agreement is observed with the MM results that employed PBCs. Hence, we have concluded that the proposed MM modeling approach is equivalent to MM models that employed PBCs. The computed enhanced effective elastic, piezoelectric, and dielectric properties and corresponding figure of merit revealed that 1–3 PCs are suitable in transducer applications.